Hubungan Kecerdasan Emosi dengan Insomnia pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Sebelas Maret Surakarta - Nurharyani, Fitria Rahma; Fanani, Mohammad; Probandari, Ari Natalia (Nexus Kedokteran Klinik, 2014)
Background: Insomnia was the most frequently sleep disorder; even for adolescents, and college students. Insomnia was caused by many factors including emotion. The low emotional intelligence could lead individuals to be vulnerable to stress and the manifestation of stress included anxiety and depression that caused insomnia. This research aimed to identify the correlation between emotional intelligence and insomnia among Medical Students in Faculty of Medicine, Sebelas Maret University. Method: This study was an analytical descriptive study with cross-sectional approach conducted from October to November 2013 in Faculty of Medicine, Sebelas Maret University. The sample was taken using total sampling technique after having been selected using inclusion and exclusion criteria of research. The sample could not be included if the questionnaire was incomplete. The subject filled in (1) informed consent and personal data form, (2) L-MMPI questionnaire, (3) Insomnia Rating Scale questionnaire to find out the insomnia score, (4) Emotional intelligence questionnaire to measure the emotional intelligence score of sample. Totally, there were 128 sample subjects. The data were analyzed using Spearman Correlation test with SPSS 17.00 for Windows program. Result: The statistical analysis showed the Spearman correlation score (r) = -0.094 and p = 0.146 or p > 0.05, it meant that the correlation between emotional intelligence and insomnia of Medical Students in Medical Faculty of Surakarta Sebelas Maret University was not significant. Conclusion: There is no correlation between emotional intelligence and insomnia of Medical Students in Medical Faculty of Sebelas Maret University. Keywords: emotional intelligence, insomnia, medical students.Â